PENINGKATAN KEMAMPUAN PEMAHAMAN DAN ANALISIS MASALAH PADA PSIKOLOGI FAAL MELALUI PEMBELAJARAN BERBASIS AKTIVITAS - Ambar Sulianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research aims to know the effect of learning based activity toward understanding of concepts and problem analysis in psyco-pshysiology class of pshycology faculty, Islamic state university. Participants are 68 first year students which are divided into control group and treatment group. 34 students of control group have lecturing and multimedia non animated method while other 34 studends of treatment group have activity based learning method. Data were analyzed using Independent T-Test. Result shows that activity based learning method improve the understanding of concepts and problem analysis ability.